Africa RISING Baseline Evaluation Survey (ARBES) report for Malawi - Shee, Apurba; Azzarri, Carlo; Haile, Beliyou; Comanescu, M.; Roberts, C.; Signorelli, S. (International Food Policy Research Institute, 2016)
This report presents overall summaries of Malawi Africa RISING Baseline Evaluation Survey (MARBES) data that cover 1,149 households in Africa RISING areas in central region of Malawi covering two districts (Dedza and Ntcheu). Following a description of survey design and tools, the report presents main findings in the form of cross tabulation, tables and graphs for both household and community level survey data. The summaries of the household data include demography, agricultural land characteristics, production and inputs, storage facility, livestock ownership, dwelling characteristics, agricultural related shocks, and children and women anthropometry. The community data summary covers community demography, access to basic services, labor in agriculture, agriculture related problems and solutions, land use and major crops, migration, availability of water resources, and prevalence of shocks